Bowel Arteriovenous Malformation: An Unusual Cause of Lower Gastrointestinal Bleeding in a Child - Govindarajan,Krishna Kumar (2021)
Abstract: In a child, lower gastrointestinal tract bleeding can be attributed to different etiologies. Unusually, the presence of bowel arteriovenous malformations can lead to multiple bouts of painless bright red bleeding per rectum, which develop into severe anemia. The article focuses on the diagnosis and management of bowel arteriovenous malformation in a child.